Enhanced enzymatic hydrolysis and acetone-butanol-ethanol fermentation of sugarcane bagasse by combined diluted acid with oxidate ammonolysis pretreatment. (March 2017) - Li, Hailong; Xiong, Lian; Chen, Xuefang; Wang, Can; Qi, Gaoxiang; Huang, Chao; Luo, Mutan; Chen, Xinde
Highlights: A novel and combined DA with OA pretreatment was proposed for the biorefinery of SB. The enzymatic hydrolysis of SB was improved by the combined DA with OA pretreatment. The production of ABE was enhanced by the combined DA with OA pretreatment. An excellent humus fertilizer was produced by the combined DA with OA pretreatment. Abstract: This study aims to propose a biorefinery pretreatment technology for the bioconversion of sugarcane bagasse (SB) into biofuels and N-fertilizers. Performance of diluted acid (DA), aqueous ammonia (AA), oxidate ammonolysis (OA) and the combined DA with AA or OA were compared in SB pretreatment by enzymatic hydrolysis, structural characterization and acetone-butanol-ethanol (ABE) fermentation. Results indicated that DA-OA pretreatment improves the digestibility of SB by sufficiently hydrolyzing hemicellulose into fermentable monosaccharides and oxidating lignin into soluble N-fertilizer with high nitrogen content (11.25%) and low C/N ratio (3.39). The enzymatic hydrolysates from DA-OA pretreated SB mainly composed of glucose was more suitable for the production of ABE solvents than the enzymatic hydrolysates from OA pretreated SB containing high ratio of xylose. The fermentation of enzymatic hydrolysates from DA-OA pretreated SB produced 12.12 g/L ABE in 120 h. These results suggested that SB could be utilized efficient, economic, and environmental by DA-OA pretreatment.